Differences in the amplitude of dynamic low-frequency fluctuations in primary angle-closure glaucoma are associated with gene-molecular multi-omics - Hu, Yuan; Hu, Rui-Yang; Yang, Hai-Jun; Xu, Ting-Ting (Frontiers in Medicine, 2025)
ObjectivePrimary angle-closure glaucoma (PACG), an incurable ophthalmic disease, is a serious risk to human visual health. Previous studies have demonstrated a strong link between PACG and neuroimaging changes in the brain. This study utilizes dynamic low-frequency fluctuation amplitude (dALFF) with the aim of resolving the potential dynamic alterations in neurological function in PACG and integrating transcriptomics profiles with spatial distribution characteristics of neuromodulatory receptors/transporters to systematically elucidate the underlying neurophysiopathological mechanisms.MethodsWe used sliding time windows of 30TR, 50TR and 80TR to calculate dALFF values and performed partial least squares regression (PLS) analysis of t-values after two-sample test of dALFF values under the sliding window of 50 TR against the Allen Human Brain Atlas (AHBA) to screen genes. Enrichment analysis, tissue-specific expression analysis and protein–protein interactions (PPI) network construction were implemented. The t-values were also analyzed for spatial correlation with neurotransmitter receptor/transporter density profiles distributed throughout the brain.ResultsThe two-sample tests under three sliding windows revealed extensive brain alterations in PACG and each abnormal brain region showed elevation (the Gaussian Random Field method, with significance at the voxel level set at p < 0.005 (two-tailed) and at the cluster level at p < 0.01), which was mainly in the occipital lobe and angular gyrus. Enrichment analysis were mainly “regulation of neuron projection development” and “membrane organization” pathways (p < 0.05, no corrected). Specific expression analysis revealed that the relevant genes were involved in all stages of thalamic development. PPI analysis demonstrated the role of PACG-associated genes in the formation of functional network. Neurotransmitter receptor/transporter correlation analysis revealed significant associations with 5-HT4R and mGlu5R (p < 0.05, FDR corrected).ConclusionThe present study reveals that a wide range of brain regions in PACG patients show significant functional remodeling, elucidating the molecular regulatory network behind this type of pathological alteration.